A comparative civilizational reading for the Middle East and Turkey's new role in it. Issue 1 (2nd January 2016) - Ataç, C. Akça
ABSTRACT: The 1990s witnessed a bloom of studies on the 'standard of civilization', which all aimed to explore the future of the rift between the East and the West. The Arab Spring and its implications for the primordial competition between the East and the West has once again required the revisiting of certain, rather more contemporary, theoretical aspects of the grand debate on civilization. This paper aims to introduce current arguments pertaining to the grand debate on civilization into the context of the Arab Spring. In doing so, it seeks to offer a comparative perspective of the quest for understanding the current situation in the Middle East with particular reference to the civilization discourse which is currently on the rise in Turkish politics. Turkey is among the actors in the Middle East seeking to assume leadership in order to establish peace in the region.